The Influence of Earning Per Share, Price to Book Value, Return on Asset, and Return on Equity to Stock Price in Finance Company - Cahyaningrum, Yustina Wahyu; Antikasari, Tiara Widya (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2017)
Abstract: The Influence of Earning Per Share, Price to Book Value, Return on Asset, and Return on Equity to Stock Price in Finance Company. The research purpose is to examine the influence of EPS, PBV, ROA and ROE to stock price simultaneously or partially in finance sector companies listed on Indonesia Stock Exchange (BEI) in 2010-2014. The research using secondary data based on the annual report taken from Indonesia Capital Market Directory and Indonesia Stock Exchange and other support sources. This study uses purposive sampling and 237 of 255 finance sector companies listed in ICMD used as the sample. This research uses multiple regression analysis. The research result shows that EPS, PBV, ROA, and ROE in 2010-2014 simultaneous and partially positive significantly affected by the stock price. Keyword: Earning Per Share, Price to Book Value, Return on Asset, Return on Equity, Stock Price.Abstrak: Pengaruh Earning Per Share, Price to Book Value, Return on Asset, dan Return on Equity Terhadap Harga Saham Sektor Keuangan. Penelitian ini mempunyai tujuan untuk mengetahui pengaruh Earning Per Share (EPS), Price to Book Value (PBV), Return on Asset (ROA), Return on Equity (ROE) secara simultan maupun parsial terhadap harga saham pada perusahaan sektor keuangan yang terdaftar di Bursa Efek Indonesia tahun 2010-2014. Penelitian ini menggunakan data sekunder berupa laporan keuangan tahunan yang diperoleh dari ICMD dan sumber pendukung yang lain. Teknik pengambilan sampel diambil dengan metode purposive sampling sebanyak 237 perusahaan sektor keuangan dari 255 perusahaan yang terdaftar di ICMD. Data dianalisis dengan analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa variabel EPS, PBV, ROA, dan ROE tahun 2010-2014 secara simultan dan parsial mempunyai pengaruh positif terhadap variabel harga saham. Kata Kunci: Earning Per Share, Price to Book Value, Return on Asset, Return on Equity, Harga Saham